Microstructure and mechanical properties of friction stir welded thick pure copper plates - Azizi, A.; Barenji, R. Vatankhah; Barenji, A. Vatankhah; Hashemipour, M. (Springer London Ltd, 2016)
In this study, 10-mm-thick pure copper plates were friction stir welded at a constant rotational speed of 700 rpm and different traverse speeds of 50, 100, 150, and 200 mm/min using a square pin profile tool. The thermal cycles and peak temperatures were recorded using accurate thermocouples. In addition, the microstructural features of the joints were examined by optical microscopy. Furthermore, for analyzing the mechanical performance of the joints, hardness and tensile tests were conducted. In addition, the fractography of the joints was done using a scanning electron microscope. The results showed that higher traverse speeds caused lower heat input and peak temperature and hence finer grains. Furthermore, higher traverse speeds lead to formation of the defects in the joints. With increasing the traverse speed, the ultimate tensile strength of the joints increased to a maximum value and then decreased. Likewise, with increasing the traverse speed, the hardness and elongation of the joints increased and decreased, respectively. Additionally, the joints welded at lower traverse speeds revealed more ductile fracture mode.
Keywords: Friction stir welding; Thick copper plates; Peak temperature; Microstructure; Mechanical properties